Sleep and Learning: The Magic That Makes Us Healthy and Smart - Plaford, Gary R. (Rowman & Littlefield Publishers, 2009)
The gradual and cumulative sleep deprivation that many students endure not only makes them too tired to focus well but also hampers memory consolidation and motivation. If we really want to improve school performance and graduation rates, we cannot afford to overlook something as basic and critical as sleep. Additionally, if we want to make an impact on both the physical and mental health of individuals in our society (which impacts mortality rates, health care, health insurance rates, the aging process, etc.), we need to begin by educating our youth about the relevance of sleep.